Instrinsic Religiosity mempengaruhi Niat Beli Produk Halal - Yudha Trishananto; Zabrina Chandra Devi (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to determine the effect of Intrinsic Religiosity, Knowledge of Halal Products on Intention to Purchase Halal Products with Halal Product Awareness as a mediating variable. The technique used is purposive sampling technique. The results showed that the intrinsic religiosity variable had a significant effect on the intention to buy halal products, the intrinsic religiosity variable and knowledge of halal products had a significant effect on halal product awareness. The variable knowledge of halal products is not significant to the variable of purchase intention of halal products. Halal product awareness mediates intrinsic religiosity and knowledge of halal products on the purchase intention of halal products produk.